PENGARUH TERAPI AL-QUR’AN SURAH AL-FATIHAH UNTUK MENGURANGI KECEMASAN KOMUNIKASI SISWA MELALUI BIMBINGAN KELOMPOK DI SMA NEGERI 12 PEKANBARU - Nadia Putri; Tri Umari; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstarak: this study aims to determine the differences in communication anxiety before and after being given the therapy of the Qur'an surah Al-Fatihah through group guidance and knowing the effect of the therapy of Al-Qur'an surah Al-Fatihah to reduce students' communication anxiety through group guidance. This research was conducted at Pekanbaru State High School 12 against 8 subjects with purposive sampling technique. The research design was pre-experiment with the one group pre-test post-test model. The instrument of data collection used was a communication anxiety questionnaire adapted from Miles and Vicky (2009). The results showed that there were differences in students' communication anxiety before and after being given Al-Qur'an surah Al-Fatihah therapy with a significant value of 0.012 <0.05. in addition, based on the Spearman rank test, it is known that there is a significant influence between the therapy of Al-Qur'an surah Al-Fatihah on student communication anxiety with a significant value of 0.001 <0.05. The influence of Al-Qur'an surah Al-Fatihah therapy on student communication anxiety is 86.11% while 13.89% is influenced by other factors that come from within and from the student's environment. From the results obtained, it is recommended that educational institutions should be able to continue implementing IMTAQ such as relaxation, reading the Qur'an correctly by living it, deepening the Qur'an and religious learning to encourage the development of thoughts, perceptions, insights, calmness and attitudes more positive students. Key Words: Al-Qur'an Surah Al-Fatihah, therapy, Communication Anxiety,